Penerapan Handout Digital Pada Elemen Dasar Konstruksi Bangunan Dalam Upaya Peningkatan Hasil Belajar Siswa Jurusan Dpib Kelas X SMK Negeri 1 Kemlagi - Naufal Dhiya Ulhaq; Soeparno Soeparno (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to determine: (1) the implementation of the direct learning model assisted by digital handout teaching materials; (2) the difference in learning outcomes between students who use the direct learning model assisted by digital handouts and students who use the direct learning model without digital handouts. The type of research used in this study is Quasi-Experimental Design employing experimental and control groups with a quantitative approach. The instruments used in this study are pre-test, post-test, and validation questionnaires to assess the feasibility of digital handouts through expert validation. The research results obtained that: (1) The average percentage of implementation in the teacher domain and student domain from 2 meetings was 87%. This value falls within the interval of 76% - 100% with a very good interpretation. This indicates that the percentage of implementation of the use of digital handout teaching materials was well executed with a percentage result of >75%. (2). The results of the independent t-test analysis in this study showed a Sig. (2-tailed) value of <0.001, which is less than 0.05, meaning that Ho is rejected and Ha is accepted. Therefore, it can be concluded that there is a very significant difference between the posttest learning outcomes of the experimental class students and the control class students. This test result is supported by the difference in the average percentage increase between the experimental class and the control class, where the average percentage value of the experimental class (115.89%) is greater than the average percentage value of the control class (99.73%).